2011
DOI: 10.6090/jarq.45.211
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Antimutagenicity of Thermal Processed Thai Foods

Abstract: Ten different foods containing local Thai vegetables were selected to study their antioxidant and antimutagenic properties. The antioxidant capacity, antimutagenicity, and total phenolic content of methanol extracts obtained from cooked food samples exhibited a wide variation ranging from 24-140 mg vitamin C equivalent/100 g, 53-93% and 35-125 mg gallic acid equivalent/100 g. The three foods highest in antioxidant capacity were Kaeng Hoi Bai Chaplu (wild betal curry), Phat Sator (stirfried petai beans), and Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
18
1
1
Order By: Relevance
“…Both compounds were found to be higher in the ethanolic extract than the methanolic extract [10, 18], which could be due to more hydrophobic compounds being retained in the ethanol compared to the methanol extract. This is further shown in two different studies [18, 34] where the total phenolic content was totally absent in the former study [18] but detected at a larger content in the latter study [34]. There are many factors that may affect the chemical content or composition in plants such as species, method of extraction, storage condition, and season and age of the plant parts at the time of harvest as well as geographical factors.…”
Section: Properties Of P Speciosamentioning
confidence: 70%
See 1 more Smart Citation
“…Both compounds were found to be higher in the ethanolic extract than the methanolic extract [10, 18], which could be due to more hydrophobic compounds being retained in the ethanol compared to the methanol extract. This is further shown in two different studies [18, 34] where the total phenolic content was totally absent in the former study [18] but detected at a larger content in the latter study [34]. There are many factors that may affect the chemical content or composition in plants such as species, method of extraction, storage condition, and season and age of the plant parts at the time of harvest as well as geographical factors.…”
Section: Properties Of P Speciosamentioning
confidence: 70%
“…Much attention has been paid to explore any potential antitumor agents in edible plants, for future use in humans. Amongst many medicinal plants screened, the methanolic extract of P. speciosa seeds demonstrated a moderate antimutagenic activity in the Ames test [34], while in inhibition assay of Epstein-Barr virus (EBV), the antitumor promoting activity of the seeds was considered as weakly active [50]. Nevertheless, it had been reported that consumption of the raw seeds reduced the incidence of esophageal cancer in Southern Thailand [51].…”
Section: Properties Of P Speciosamentioning
confidence: 99%
“…Dietary intake of raw seeds was also reported to significantly lower the occurrence of esophageal cancer in southern Thailand [ 167 ]. The methanol extract of P. speciosa seeds exhibited a moderate antimutagenic activity in the Ames test [ 168 ], but weak activity in Epstein–Barr virus inhibitory assay [ 169 ]. The methanol extract of the seed coats demonstrated selective cytotoxicity against MCG-7 and T47D (breast cancer), HCT-116 (colon cancer) and HepG2 (hepatocarcinoma) cells, while its ethyl acetate fraction only showed selective cytotoxicity against MCF-7, breast cancer cells [ 170 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%
“…This phenomenon was due to the increase in pressure as the density of CO2 was higher, causing the penetration of CO2 into matrix solid to become easier [15]. Therefore, the Publishing mass transfer increased according to the increase of pressure [1].…”
Section: Antioxidant Activitymentioning
confidence: 96%